Corporate Social Responsibility Disclosure on Return on Equity Processed Food Companies that Listed at Indonesian Stock Exchange 2017 – 2020 Year Period - Aris Baharuddin; St. Chairun Annisa Yusran (Universitas Negeri Makassar, 2022)
One of the efforts that the company can do to improve its image is by disclosing a corporate social responsibility report in an annual report which is published to the public every year. This study aims to determine how the influence of Corporate Social Responsibility disclosure on company profitability as a proxy for Return on Equity (ROE) where Processed Food companies are listed on the Indonesia Stock Exchange for the period 2017-2020 as the object of research. This research is a type of quantitative research. The data collection technique used is the secondary data documentation technique in the form of an annual report. The sample used is a sample selected using a purposive sampling technique as many as 4 companies so that the annual report that becomes the object of as many as 16 annual reports. The data obtained from the research results were processed using the SPSS version 25 software program which consisted of Simple Linear Regression Analysis, Hypothesis Testing (T-Test), Correlation Coefficient, and Coefficient of Determination. The results show that the indicators used for each variable indicate that the CSR disclosure variable has a significant effect on the ROE of processed food companies listed on the IDX for the period 2017-2020. This is evidenced by Simple Linear Regression Analysis, Hypothesis Testing (T-Test), Correlation Coefficient, and Coefficient of Determination on the data that has been obtained.